2020
DOI: 10.1016/j.crtox.2020.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Sub-chronic dermal exposure to aircraft engine oils impacts the reproductive organ weights and alters hematological profiles of Sprague Dawley rats

Abstract: There is little data available for the toxicity of used aircraft engine oils relative to their unused (new) versions. This study was conducted to determine if grade 3 (G3) and 4 (G4) aircraft engine oils in their new states (G3-N and G4-N) and their used versions (G3-U and G4-U) have the potential to induce toxicity via dermal application. Male and female Sprague Dawley rats were dermally exposed to water (control), new and used versions of G3 and G4 oils to determine the oil sub-chronic toxicity potentials. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…2). Organ mass has also been demonstrated to be impacted in rats following dermal exposure to engine oil (Sibomana and Mattie, 2020). AChE inhibition arising from dermal exposure of whole oil products on rats has also been demonstrated with a possible sex-linked correlation (Sibomana et al, 2021; SI-Table 3).…”
Section: Animal Exposure Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…2). Organ mass has also been demonstrated to be impacted in rats following dermal exposure to engine oil (Sibomana and Mattie, 2020). AChE inhibition arising from dermal exposure of whole oil products on rats has also been demonstrated with a possible sex-linked correlation (Sibomana et al, 2021; SI-Table 3).…”
Section: Animal Exposure Studiesmentioning
confidence: 97%
“…Eight studies were identified as animal studies, implying the use of whole animals or tissues; mice or rats or rabbits were the subjects of all studies (Baker et al 2012;Hausherr et al, 2017;Duarte et al, 2017;Naughton et al, 2020;Sibomana et al, 2019;and Sibomana & Mattie, 2020;Sibomana et al, 2021).…”
Section: Animal Exposure Studiesmentioning
confidence: 99%
“…In Nigeria, the indiscriminate disposal of SEO has led to direct and/or indirect exposures of humans, creating health risks, via dermal, oral, or inhalatory routes of exposure. Studies have shown the toxicity of used engine oil exposure to Wistar rats and mice orally (Babalola and Oni, 2018; Patrick-Iwuanyanwu et al, 2010; Wasiu et al, 2015), dermally to rabbits and rats (Sibomana et al, 2019; Sibomana and Mattie, 2020), and to aquatic organisms such as Clarias gariepinus (Ayoola and Akaeze, 2012).…”
Section: Introductionmentioning
confidence: 99%